Government debt indicators Understanding the data - Bloch, Debra (OECD Publishing, 2015)
There is no single "best" indicator for analysing general government debt. This paper examines the various issues in defining and measuring debt, and explores other data which could be useful, both within and beyond the general government debt concept, to better track and analyse fiscal risks and sustainability issues. Measures from the broadest view of debt - gross financial liabilities - to the most comprehensive accounting of asset and liability positions - net worth - are all helpful metrics. So, too, are narrower data on specific issues, such as future pension liabilities, government guarantees and debt composition. Better data reporting, including more complete metadata and broader data collection, are needed to allow for an arsenal of comparable debt concepts to better anticipate future fiscal pressures
Keywords: Economics